2008
DOI: 10.1063/1.2823561
|View full text |Cite
|
Sign up to set email alerts
|

Thermodiffusion in nanofluids under different gravity conditions

Abstract: A convective transport model is developed to study the role of thermal diffusion, or the Ludwig–Soret effect, in nanofluid systems with temperature gradients. The study deals with a fluid suspension of nanoparticles enclosed between two differentially heated horizontal, relatively closely spaced plates (Bénard configuration). An order-of-magnitude analysis is performed to identify the relevant parameters of the problem. Three-dimensional simulations are performed taking into account different conditions, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Previous studies have evaluated D B , D T using some reference temperature and volume fraction, whilst allowing T, φ to vary everywhere else in the equations, see for example (Buongiorno 2006;Savino and Paterna 2008). To clarify the dependence on temperature and volume fraction in all subsequent equations we will use constants that do not involve T, φ, i.e.…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have evaluated D B , D T using some reference temperature and volume fraction, whilst allowing T, φ to vary everywhere else in the equations, see for example (Buongiorno 2006;Savino and Paterna 2008). To clarify the dependence on temperature and volume fraction in all subsequent equations we will use constants that do not involve T, φ, i.e.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Evans et al (2006) concluded that Brownian motion has a negligible effect on the thermal conductivity. Savino and Paterna (2008) study buoyancy driven flow in a 1mm wide channel, they conclude that Brownian motion and thermophoresis do affect the flow, but only over a time-scale of 27 hours, with the results most noticeable when gravity is 10 −6 of its normal value. The real goal in the development of nanofluids for cooling purposes is to enhance the heat transfer and energy removal from a given surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Savino and Paterna [76] modeled convective transport of nanofluids subjected to thermal diffusion in a temperature gradient between two differently heated parallel plates. They showed that the combination of concentration and thermal gradients could create circulation based on the orientation of the cell.…”
Section: Particle Diffusionmentioning
confidence: 99%
“…Specific details of this idea in thermal convection in a porous medium may be found in Nield & Bejan (2006, p. 31), Nield (2002), Nield & Kuznetsov (1999), Banu & Rees (2002) and Malashetty et al (2005), and in the nonlinear case in Straughan (2006). Current theories for nanofluid behaviour (see Savino & Paterna 2008;Tzou 2008;Kuznetsov & Nield 2010, in press) all assume the fluid to be Newtonian. However, there is clear evidence in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%